The Effect of Length of Injury on the Success of Effriction Massage in Knee Injury Rehabilitation - Cahulul Rizaldy Hasan; Andry Akhiruyanto; Arif Setiawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study evaluated the effectiveness of effriction massage in reducing pain and increasing range of motion (ROM) in patients with knee injuries based on the duration of injury. Using a prospective controlled clinical trial involving 20 participants aged 20 to 40 years, participants were grouped into two groups: acute (10 days) and chronic (1 month) injuries. The effriction massage intervention was performed for 15 minutes, and outcomes were measured using the Visual Analog Scale (VAS) for pain and the goniometer for ROM. Results showed significant pain reduction in both groups, with the chronic group obtaining a greater reduction (58.33%) than the acute group (44.44%). However, the increase in ROM showed significant variation, with the chronic group increasing ROM by 21.64%, while the acute group increased by 21.02%. Analysis showed that duration of injury had no significant effect on pain (p=0.334), but did affect ROM (p=0.035). These findings confirm the importance of early intervention and the implementation of rehabilitation tailored to the chronicity of the injury, opening up opportunities for developing more individualized therapy guidelines. This study recommends the integration of additional modalities for longer injury cases to improve rehabilitation outcomes.